2012
DOI: 10.1161/atvbaha.111.234872
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in ABCG1 and Risk of Myocardial Infarction and Ischemic Heart Disease

Abstract: Objective-ATP binding cassette transporter G1 (ABCG1) facilitates cholesterol efflux from macrophages to mature high-density lipoprotein particles. Whether genetic variation in ABCG1 affects risk of atherosclerosis in humans remains to be determined. Methods and Results-We resequenced the core promoter and coding regions of ABCG1 in 380 individuals from the general population. Next, we genotyped 10 237 individuals from the Copenhagen City Heart Study for the identified variants and determined the effect on lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…42,43 However, nothing is yet known about an epigenetic impact of ABCG1 on the development of MI. A human cell culture study showed a reduction of macrophage ABCG1 expression when higher triglyceride levels were present in the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 However, nothing is yet known about an epigenetic impact of ABCG1 on the development of MI. A human cell culture study showed a reduction of macrophage ABCG1 expression when higher triglyceride levels were present in the culture media.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic association studies in humans identified functional variants in ABCG1 associated with increased risk of coronary artery disease (Xu et al 2011;Schou et al 2012), suggesting an important role of ABCG1 in the protection from atherosclerosis and cardiovascular disease.…”
Section: Atp-binding Cassette Transporter G1mentioning
confidence: 99%
“…248 Little is known about the role of ABCG1 in human metabolism. Schou et al 249 reported a functional ABCG1 promoter variant that associates with increased risk of myocardial infarction and ischemic heart disease in the general population but without affecting levels of HDL-C or other lipids or lipoproteins. Abellán et al, 15 however, described a significant association between promoter variant and HDL-C levels.…”
Section: Atp-binding Cassette Transporter G1mentioning
confidence: 99%